University Students, Advertising on Digital Social Networks and Cinema: Opinions of Communication Sciences Students from a Mexican Public University in Relation to their Film Consumption Preferences - Ortiz Alvarado, Francisco Jesús; Espinosa Castañeda, Raquel; Barrales Martínez, Alfredo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
It is analyzed the influence of social media advertising on audience perception and decision-making regarding film consumption. Through a survey-based methodology, data was collected from young adults to assess the persuasive impact of such advertisements. The results reveal that platforms like Instagram and TikTok are dominant channels for movie promotions. Also is highlighted the extent to which digital advertising influences movie selection. These findings contribute to the understanding of contemporary advertising strategies and provide insights into optimizing promotional efforts in the digital era. The study also suggests potential applications in academic curricula and professional training programs.